PERANCANGAN SISTEM TERINTEGRASI UNTUK EFISIENSI OPERASIONAL PADA BIUS COFFEE DENGAN METODE SCRUM - Suprianto Suprianto; Nabilah Nurul Hikmah; Nikken Aidilya Savitri; Hafizhan Zulhilmi (Journal of Innovation And Future Technology, 2026)
An integrated system is essential to improve operational efficiency in various sectors, including Bius Coffee. Issues such as long queues at the cashier and order errors arise due to the lack of connectivity among customers, cashiers, cooks, and waiters. To address these problems, a web-based integrated system was designed using the Scrum method, an Agile approach that emphasizes flexibility, adaptability, and team collaboration. The Scrum stages applied include the development of user stories, product backlog, and sprint backlog. A needs analysis was conducted on Bius Coffee’s operational processes, followed by system design using Unified Modeling Language (UML), which covers use case, activity diagram, class diagram, and prototype interface. The application of Scrum facilitates task distribution based on priority and more accurate time estimation. The design results show that the system enables customers to place orders directly, cashiers to validate orders quickly, and cooks to access orders in a more organized manner. Therefore, this system has the potential to improve both work efficiency and service quality at Bius Coffee.